Língua, patrimônio cultural: um estudo sobre o dialeto alemão falado na cidade de Agudo - Pachaly Filho, Rolf (2024)
The present work focuses on the region of Agudo, a small city in the center of Rio Grande do Sul, which is part of a set of nine municipalities of immigration, the Fourth Colony. The general objective of this project is to disseminate, rescue and conserve the German culture and language in the city of Agudo-RS and in the region, through a Technical Product in order to offer the dissemination of the German language to the visiting community of the recently named Quarta Colônia Geopark as a world heritage site by UNESCO. In this way, it is expected to value tourism in the region, as well as to rescue the customs of our ancestors to consolidate this intangible heritage, which is the spoken language, so that it does not become lost in the community's memory. The research undertaken is qualitative in nature and has an interpretative and subjective character, to complement the information obtained through the narrative review, field research was carried out with students from an elementary school in the region. Responding directly to the objectives of the research, it can be inferred that success was achieved in the celebration and preservation of the German language and culture in Agudo-RS, and it is possible to highlight a rich range of experiences that resonate with the authentic essence of the German heritage, creating a mosaic of local cultural engagement. The creation of a bilingual brochure, German and Portuguese, emerges as a strategic initiative, making the cultural wonders of Agudo accessible and inviting, across a linguistic and cultural bridge. This material, distributed with consideration and intentionality, will act as a compass, guiding visitors through the tourist and cultural richness of the region. The present study is part of the History and Cultural Heritage concentration area, of the Postgraduate Program in Cultural Heritage, at the Federal University of Santa Maria, in the History and Cultural Heritage research line.